Elaboración de un plan de mantenimiento para una grúa tipo celosía bucyrus 38-B de la empres Subsuelos S.A.S. en Cota-Cundinamarca (2020)
In order to achieve the full development of the project presented below, entitled "Development of a maintenance plan for a lattice crane of the Subsuelos SAS in Cota-Cundinamarca" began by characterizing the crane systems to gain knowledge of the elements and components present, after this, through field visits to the maintenance workshop, a diagnosis of the systems was given, thus knowing the current state of the machine, once this was determined, a criticality analysis was carried out to determine which systems are more critical than others and in what order the maintenance plan should be implemented, an evaluation was carried out between the maintenance strategies TPM, RCM and FMEA to establish which of these best suited the operational tasks and condition of the crane. After having carried out the evaluation of strategies, it was concluded that the most appropriate for this machine is the failure mode and effect analysis, then this strategy was implemented to carry out the maintenance plan, different failure modes were established to perform the respective FMEA to the systems, in the same way lubrication and inspection tasks were assigned to the maintenance program where factors such as time, the place of repair, the person in charge and different aspects that allow to better carry out this task plan are taken into account scheduled.